Fine-tuning properties of biocompatible carbon-polymer composites; СХС-2025 - Sheremet E. S. Evgeniya Sergeevna; Petrov I. S. Iljya Sergeevich; Fatkullin M. I. Maksim Ilgizovich; Abyzova E. G. Elena Gennadievna (2025, 2025)
Текстовый файл